Professionals, wives and mothers. Women college graduates of Universidad del Pacífico, 1980-1985 - Kogan, Liuba (1994)
This essay is the result of a research project about the current position of women who studied at Universidad del Pacífico between 1980 and 1985. It describes the difficulties they encountered, and strategies they developed when applying for jobs. It is based on interviews using standardized questionnaires. The following pages show the results of the research.